2021
DOI: 10.33380/2305-2066-2021-10-3-138-146
|View full text |Cite
|
Sign up to set email alerts
|

Procedure for Reviewing Pharmaceutical Inspections in the Eurasian Economic Union (Review)

Abstract: Introduction. The article discusses significant changes in the procedure for pharmaceutical inspection of drug manufacturers for compliance with the requirements of the rules of good manufacturing practice (GMP) of the Eurasian Economic Union (EAEU), related to restrictions due to the COVID-19 pandemic.Text. The article presents the main international guidelines describing the remote conduct of pharmaceutical inspections, which is the basis for further updating the relevant procedures in the law of the EAEU. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…[ 31 ] studied the peculiarities of the functional state of kidneys at RA. It was found that GFR in such patients decreased by 0.83 mL/min per year (95% CI −1.08 to −0.57) [ 32 , 33 ]. The study of Hickson et al.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] studied the peculiarities of the functional state of kidneys at RA. It was found that GFR in such patients decreased by 0.83 mL/min per year (95% CI −1.08 to −0.57) [ 32 , 33 ]. The study of Hickson et al.…”
Section: Discussionmentioning
confidence: 99%
“…This monocyteendothelial interaction as one of the principal triggering mechanisms of atherogenesis is directly related to free radical oxidation of lipids and oxidative stress. By penetrating the vascular intima, monocytes accumulate oxidized lipids and become foamy cells that secrete some biologically active substances that are critical atherogenesis processes [28,29]. These are, in particular, such proinflammatory mediators as Eselectin, endothelial cell adhesion molecules-1, intercellular adhesion molecules-1, and others.…”
Section: Introductionmentioning
confidence: 99%